Factors Affecting Employee Job Satisfaction in Bhaktapur Municipality Office - Prajapati, Nabin; Khuju, Jamuna (Khwopa Journal, 2023)
Job satisfaction is the crucial requirement for ensuring the efficient operation of the organization. Several scholars across various fields have used the construct of job satisfaction as a focus of their research. This study is aims to identify the factors affecting the job satisfaction of employees. Among the 585 employees working in Bhaktapur Municipality, 100 employees were selected based on disproportionate stratified sampling to collect information using structured questionnaire. Descriptive and analytical research design was used. Correlation and regression analyses were used to check the hypothesis. The findings indicate different factors like the working environment, the task itself, job security, wages, pay, and grades have a significant effect on job satisfaction, whereas recognition and supervision have a positive but insignificant effect on it. Among different factors, wages, pay, and grades have a higher effect on job satisfaction. This study provides a roadmap for higher authorities to apply different techniques to satisfy their employees.